Wind tunnel test research for influence of passive flow control technology on low speed characteristics of civil transport aircraft - YAN Wei; WANG Qimin; LI Jinye; XU Huiwen; ZHAO Keliang; BAI Feng; ZHANG Meihong; JIAO Renshan; WANG Fei; ZENG Weiping (Hangkong gongcheng jinzhan)
In order to optimize the low-speed characteristics of the high-lift configuration of civil transport aircraft and enhance the take-off and landing performance of the aircraft，it is necessary to control the flow separation of the wings. Through the wind tunnel test，the research on the selection of two passive control technologies，the wingbody fairing and outboard nacelle strake，is carried out. The best combination scheme that can optimize the lowspeed characteristics is found：small size wing-body fairing plus outboard nacelle strake "A"；the area where the flow separation is suppressed by the optimization method is presented through the flow visualization test. The pitch moment characteristics under the conditions of the optimal combination scheme meet the requirements of Boeing criteria.